2021
DOI: 10.1002/anie.202101511
|View full text |Cite
|
Sign up to set email alerts
|

Nitrone and Alkyne Cascade Reactions for Regio‐ and Diastereoselective 1‐Pyrroline Synthesis

Abstract: The synthesis of 1-pyrrolines from N-alkenylnitrones and alkynes has been explored as ar etrosynthetic alternative to traditional approaches.T hese cascade reactions are formal [4 + 1] cycloadditions that proceed through ap roposed dipolar cycloaddition and N-alkenylisoxazoline [3,3']sigmatropic rearrangement. Av ariety of cyclic alkynes and terminal alkynes have been shown to undergo the transformation with N-alkenylnitrones under mild conditions to provide the corresponding spirocyclic and densely substitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 111 publications
0
14
0
Order By: Relevance
“…[37] This reactivity pattern was not accessible for 12 a.T he connectivity and stereochemistry of 26 and 27 were confirmed by X-ray crystallographic analysis of 27. [18] Finally,a ni nteresting transformation was observed with extended reaction times for the formation of 12 b.Asshown in Scheme 8B,lactone 28 is formed in good yield and high diastereoselectivity.Further experimentation showed that 28 could also be obtained directly from 12 b by treatment with K 2 CO 3 under the cascade reaction conditions.T he transformations illustrated in Scheme 8showcase the utility of cascade reaction for accessing highly substituted and stereodefined pyrrolines that can be easily converted into avariety of molecules with increased complexity using simple procedures.…”
Section: Methodsmentioning
confidence: 92%
See 4 more Smart Citations
“…[37] This reactivity pattern was not accessible for 12 a.T he connectivity and stereochemistry of 26 and 27 were confirmed by X-ray crystallographic analysis of 27. [18] Finally,a ni nteresting transformation was observed with extended reaction times for the formation of 12 b.Asshown in Scheme 8B,lactone 28 is formed in good yield and high diastereoselectivity.Further experimentation showed that 28 could also be obtained directly from 12 b by treatment with K 2 CO 3 under the cascade reaction conditions.T he transformations illustrated in Scheme 8showcase the utility of cascade reaction for accessing highly substituted and stereodefined pyrrolines that can be easily converted into avariety of molecules with increased complexity using simple procedures.…”
Section: Methodsmentioning
confidence: 92%
“…Ther elative stereochemistry of these compounds was confirmed by X-ray crystallographic analysis of 14 j. [18] In contrast to 14 c,1 -pyrroline 14 l was resistant to isomerization in solution. Nitrones prepared from N-methylisatin and acenapthylenedione were unreactive with terminal alkynes suggesting that some amount of strain release is required to initiate the cascade reaction for these substrates.…”
Section: Angewandte Chemiementioning
confidence: 89%
See 3 more Smart Citations